2011
DOI: 10.1021/jp2035339
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Ring Orientation in Polythiophene Field-Effect Transistors on Functionalized Dielectrics

Abstract: The impact of surface chemistry on interfacial molecular orientation is studied for polymeric organic field-effect transistor (oFET) assemblies using vibrational sum frequency generation (VSFG) spectroscopy. The carbonÀ carbon vibrational modes on the backbone of side-chain deuterated poly(3hexylthiophene) (DP3HT) are demonstrated to be an excellent handle for molecular orientation. DP3HT is utilized to avoid overlap in this spectral region with alkyl CH bending vibrations. Raman and FTIR spectroscopies are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(107 citation statements)
references
References 58 publications
10
96
0
1
Order By: Relevance
“…A molecular order investigation via SFG-VS on the interface between P3HT and different functionalized silica (SiO 2 ) surfaces concluded that surface chemistry directly influences the π-stacking arrangement, which, in turn, correlates with fieldeffect mobilities of polymeric transistors. 20 Similar conclusions were reached by an investigation that combined X-ray diffraction to probe polymer crystallinity and SFG-VS to evaluate the quality of surface functionalization. 21 On the basis of a quantitative analysis, a recent report 10 used SFG-VS to determine the molecular orientation of P3HT rings on SiO 2 and AlO x substrates, both for as-cast samples and after thermal annealing.…”
Section: Introductionsupporting
confidence: 53%
“…A molecular order investigation via SFG-VS on the interface between P3HT and different functionalized silica (SiO 2 ) surfaces concluded that surface chemistry directly influences the π-stacking arrangement, which, in turn, correlates with fieldeffect mobilities of polymeric transistors. 20 Similar conclusions were reached by an investigation that combined X-ray diffraction to probe polymer crystallinity and SFG-VS to evaluate the quality of surface functionalization. 21 On the basis of a quantitative analysis, a recent report 10 used SFG-VS to determine the molecular orientation of P3HT rings on SiO 2 and AlO x substrates, both for as-cast samples and after thermal annealing.…”
Section: Introductionsupporting
confidence: 53%
“…Figure 2 and Table 2 present Raman spectroscopy measurements of different P3HT isotopes mixed with PCBM. Upon side-chain deuteration, the C-C inplane ring skeleton modes at 1,380 cm À 1 and the C-H symmetric stretching mode at 2,822 cm À 1 are shifted downwards by almost 20 cm À 1 because the heavier deuterium decreases the vibrational frequency 29 . The Raman shift of the C-H stretching mode is in agreement with the expected isotope shift based on the square root of the C-D/C-H mass ratio 3 , and the vibrational frequency of the C-S-C ring in-plane skeleton mode at 728 cm À 1 remains unchanged, suggesting that the vibrational modes of the thiophene backbone are not affected by side-chain deuteration.…”
Section: Resultsmentioning
confidence: 99%
“…Dry THF was used as the solvent through the synthesis. Side-chain-deuterated P3HT was obtained from adopted literature procedures by reacting of 3-bromothiophene and 1-bromohexane-d13 under refluxing 29 . 2,5-Dibromo-3-hexylthiophene-d13 was polymerized using the Kumada catalyst transfer polymerization method.…”
Section: Methodsmentioning
confidence: 99%
“…In the homodyne detection scenario, the signal I SFG is proportional to the square of x eff (2) , and the products of near IR ( I IR ) and 800nm ( I 800nm ) beam intensities. As we show below, by normalizing I SFG of the sample to a SFG signal from the reference sample, the dependence on I IR and I 800nm can be removed.…”
Section: Experimental Methods and Theoretical Backgroundmentioning
confidence: 99%
“…As we show below, by normalizing I SFG of the sample to a SFG signal from the reference sample, the dependence on I IR and I 800nm can be removed. As a result, we can directly determine x eff (2) , which contains x ijk ,n (Fig.1a),…”
Section: Experimental Methods and Theoretical Backgroundmentioning
confidence: 99%